2017
DOI: 10.7150/jca.19057
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1 alpha Correlates with Tumor-Associated Macrophages Infiltration, Influences Survival of Gastric Cancer Patients

Abstract: Background: Hypoxia was a common feature for accelerating tumor metastasis by both inducting epithelial-mesenchymal transition (EMT) of tumor cells and polarization of tumor-associated macrophages (TAMs). The association and roles between hypoxia, EMT and TAMs in the biological behavior of gastric cancer (GC) for the time being recurrence is unclear.Material and methods: hypoixa by expression of hypoxia-inducible factor-1 alpha (HIF-1α), polarized functional status of infiltrated TAMs by immunohistochemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Significant differences were observed within groups for the various SDT parameters. Tumor tissues subjected to SDT showed high expression levels of CD4, CD8, and CD68 and low expression levels of CD163, CD25, and FoxP3, which suggested that SDT could activate T cells, promote a shift from M2 to M1 macrophages and induce immune responses …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were observed within groups for the various SDT parameters. Tumor tissues subjected to SDT showed high expression levels of CD4, CD8, and CD68 and low expression levels of CD163, CD25, and FoxP3, which suggested that SDT could activate T cells, promote a shift from M2 to M1 macrophages and induce immune responses …”
Section: Resultsmentioning
confidence: 99%
“…can be used for the detection of different classes of tumor-associated macrophages (TAM), namely, M1 and M2 (immune-suppressive). 25,26 In the present study, we chose CD163 and CD68 to identify M2 macrophages and thus observed the effect of SDT on the differentiation of TAM. In addition, regulatory T cells mediating immunoregulation is one of the most important mechanisms for maintaining self-tolerance.…”
Section: Immunohistochemical Analysis Of Tumor Tissuesmentioning
confidence: 99%
“…A 2017 study by Fu et al has shown a significant correlation between the expression of the CD68 marker characteristic to TAMs and losing expression of the epithelial marker E-cadherin, as well the presence of the mesenchymal marker vimentin [146]. proposed increased TAMs infiltration and hypoxia-inducible factor-1 alpha (HIF-1α) as potential factors stimulating the induction of EMT [154]. Likewise, TAMs induce the expression of forkhead box Q1 (FOXQ1) promoting EMT with invasion and migration properties [155].…”
Section: Tumor-associated Macrophages In Gastric Cancermentioning
confidence: 99%
“…Hypoxia influences various proteins involved in angiogenesis, such as VEGF and inducible nitric oxide (iNOS), which are closely related to TAMs' function and ultimately contribute to the formation of tumor microenvironment. Mutually, regulating the M2 phenotype functions of macrophages helps to attenuate and alleviate the hypoxic state of the tumor …”
Section: Plasticity and Function Of Macrophagesmentioning
confidence: 99%